3D Printing‐Based Hydrogel Dressings for Wound Healing - Xuan Zhou; Xunzhou Yu; Tingting You; Baohua Zhao; Lanlan Dong; Can Huang; Xiaoqing Zhou; Malcolm Xing; Wei Qian; Gaoxing Luo (Advanced Science)
Abstract Skin wounds have become an important issue that affects human health and burdens global medical care. Hydrogel materials similar to the natural extracellular matrix (ECM) are one of the best candidates for ideal wound dressings and the most feasible choices for printing inks. Distinct from hydrogels made by traditional technologies, which lack bionic and mechanical properties, 3D printing can promptly and accurately create hydrogels with complex bioactive structures and the potential to promote tissue regeneration and wound healing. Herein, a comprehensive review of multi‐functional 3D printing‐based hydrogel dressings for wound healing is presented. The review first summarizes the 3D printing techniques for wound hydrogel dressings, including photo‐curing, extrusion, inkjet, and laser‐assisted 3D printing. Then, the properties and design approaches of a series of bioinks composed of natural, synthetic, and composite polymers for 3D printing wound hydrogel dressings are described. Thereafter, the application of multi‐functional 3D printing‐based hydrogel dressings in a variety of wound environments is discussed in depth, including hemostasis, anti‐inflammation, antibacterial, skin appendage regeneration, intelligent monitoring, and machine learning‐assisted therapy. Finally, the challenges and prospects of 3D printing‐based hydrogel dressings for wound healing are presented.